The Influence of English Songs on Students’ Pronunciation Skills at UPT SMP Negeri 3 Pangsid - Eka Nanda Putri; Ibrahim Manda; Buhari; Andi Sadapotto; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigated the influence of English songs on students’ pronunciation skills at UPT SMP Negeri 3 Pangsid. A quantitative approach with a quasi-experimental pre-test–post-test control-group design was employed. The participants were 27 seventh-grade students, consisting of 15 students in the experimental group and 12 students in the control group. The experimental group received pronunciation instruction through the English children’s song “Twinkle, Twinkle, Little Star,” whereas the control group was taught through conventional classroom activities. Data were collected using a pronunciation test assessing articulation, word stress, rhythm, and intonation. The data were analyzed through descriptive statistics, Shapiro–Wilk normality testing, Levene’s homogeneity testing, and an independent-samples t-test. The experimental group’s mean score increased from 42.33 in the pre-test to 72.00 in the post-test, while the control group increased only from 51.67 to 53.33. The post-test difference was statistically significant, t(25) = 3.784, p < .001, with a mean difference of 18.667. These findings demonstrate that English songs significantly improve junior high school students’ pronunciation by providing repeated, meaningful, and enjoyable exposure to English sounds and prosodic patterns. English songs are therefore recommended as an engaging instructional medium for pronunciation practice.